“Analisis Tafsir Al-Baqarah Ayat 188 dalam Rūḥ al-Ma‘ānī dan Relevansinya terhadap Fenomena Korupsi di Indonesia Kontemporer” - Misbah Misbah; Intan Anggrini; Akhmad Dasuki (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
Corruption in Indonesia has become a systemic problem that permeates the government sector and State-Owned Enterprises (SOEs), requiring a multidisciplinary approach, including an Islamic law perspective. This study aims to explore the interpretation of Surah Al-Baqarah verse 188 in the Tafsir Ruh al-Ma’ānī by al-Ālūsī and analyze its relevance to corrupt practices in Indonesia. The research method used is qualitative with literature studies through textual, thematic, and contextual approaches. The findings of the study show that tb he term al-bāṭil in the tafsir al-Ālūsī includes all forms of unlawful acquisition of property, such as budgets and bribes to law enforcers ( tudlū bihā ilal hukkām ). In addition, the phrase wa antum ta’lamūn emphasizes the existence of an element of intentionality by the perpetrator who has legal knowledge. The implications of this study emphasize that the eradication of corruption is not enough through formal legal sanctions alone, but must include strengthening spiritual integrity and heavy social sanctions to overcome the normalization of corrupt behavior in society.